Management of Residual False Lumen Flow After Thoracic Endovascular Repair in Chronic Type B Aortic Dissection - Rousseau, Hervé; Revel-Mouroz, Paul; Zadro, Charline; Dambrin, Camille; Cron, Christophe; Jaffro, Marion; Marek, Pierre; Vavasseur, Adrien; Mokrane, Fatima-Zohra (Cardiology and Cardiovascular Medicine, 2020)
Abstract not available in the source database.